Gasifikasi Biomassa Serbuk Gergaji Kayu Mahoni (Swietenia Mahagoni) untuk Menghasilkan Bahan Bakar Gas sebagai Sumber Energi Terbarukan - Astri Nurwidayati; Putri Ayu Sulastri; Destya Ardiyati; Agus Aktawan (CHEMICA: Jurnal Teknik Kimia, 2018)
Energy cannot be separated from human life. Increased energy needs for human life that are contradictory to existing fossil fuel sources can cause an energy crisis. Biomass is an alternative energy source that is environmentally friendly, economical and renewable. Biomass energy is derived from plants such as wood, rice hulls, corn head, etc. The process of converting biomass into energy can be done in several ways. They are combustion, pyrolysis, and gasification. Gasification is a technology for converting solid materials into syngas (CO, H2, and CH4) which can be used as a fuel. One of the gasifiers that have been developed is a downdraft system. The solid material we use in this study is a mahogany wood powder which has a cellulose content of up to 46.8%. Through this research, we can find out the effect of the variable of raw materials weight towards the time of flame, the quality of the fire, and the amount of gas produced. The gas produced was tested visually by lighting the fire and instrumentally tested using a tool called Chromatography Gas to determine the composition of the gas. The biggest yield syngas is 70,71% with the 18,000 seconds gas release time on the variable of mahogany wood powder weight of 3500 grams. The highest CH4 and CO Gas concentrations were 1,868% and 15.902% on the variable of 3,500 gram mahogany powder weight. While the highest concentration of H2 gas is 20.965% produced with the variable of 2,500 gram mahogany powder weight. The results of this study indicate that the more feed in the gasifier, the greater the number and composition of syngas and the longer the gas release time.